Genetic Characterization of Extended-Spectrum Beta-Lactamase (ESBL) and Metallo-Beta-Lactamase (MBL) Producing Klebsiella pneumoniae from Diabetic Foot Ulcer (DFU) - Dipak S. Kale; Geeta S. Karande; Kalpana D. Kale; Satish R. Patil; Kailas D. Datkhile (Wolters Kluwer Medknow Publications, 2024)
Background: Antibiotic resistance in common pathogenic bacteria is linked with the genetic makeup. The genetic basis of antibiotic resistance may vary in different species or pathophysiological conditions. Objectives: We studied the antibiotic resistance in Klebsiella pneumonia isolates from DFU in the western Indian population. We also studied the presence of ESBL and MBL mechanisms of antibiotic resistance along with the prevalence of the genes involved in ESBL (TEMESBL, SHVESBL, and CTX-MESBL) and MBL (NDM-1bla, KPCbla, OXA-48bla, and VIMbla) production. Results: A total of 161 K. pneumoniae isolates were analyzed; among which 50.93% were positive for ESBL and 45.96% were positive for MBL production. Most of the isolates were resistant to antibiotics used in the present study and partially resistant to Imipenem and Amikacin. There was no relation between the antibiotic resistance of the isolates and the production of ESBL or MBL mechanism of antibiotic resistance. Further, TEMESBL was the most prevalent gene in K. pneumoniae isolates followed by CTX-MESBL, NDM-1bla, SHVESBL, and KPCbla. VIMbla was the least prevalent gene found in K. pneumoniae isolates. There was no difference in the prevalence of the genes with respect to the presence or absence of ESBL and MBL mechanism of resistance. Further, there was no relation between the prevalence of the genes and antibiotic resistance in K. pneumoniae isolates. Conclusion: These results along with the literature review suggest that the prevalence of the genes involved in antibiotic resistance mechanisms are widespread in India and their distribution varies in different studies.